(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Self-service kiosks have significantly improved productivity and customer service in the food and beverage industry by providing customers with an easy ordering platform. Fast food restaurants use self-service kiosks to manage the ordering process. When utilizing this technology, users may feel more productive and at ease. The researcher aims to determine how self-ordering kiosks affect customers’ convenience and satisfaction and how satisfied they make them feel. This method of payment reduces face-to-face interaction, notwithstanding the possibility that the repeated touching of an ordering kiosk could accelerate the spread of germs. However, kiosks will require frequent cleaning. Contactless ordering is one way that fast-food joints might stay in business in the near and long term. Self- ordering devices make it simple for consumers to select food by simply glancing at the menus shown on the machine, making them feel more at ease. Data shows that the majority of the respondents are in the age group of 21-25 years old in both Fast food chains, composed of male respondents and are single, while most are self- employed. Customers assess their level of satisfaction in terms of accessibility, location, being not familiarized, and having a hard time with troubleshooting. Also, only limited ages are accessible with it; on the other hand, it is user-friendly. The challenges encountered by the assessment of the two groups and what solution was made by the management: the respondents claim that lagging machines usually stop responding to failed kiosks by some of the customers. In the McDonald’s situation, software issues may lead to certain features becoming unavailable. Customers should learn how to use the Self-Ordering Kiosks efficiently and properly. Managers must ensure that the available kiosks in their store are working properly and doing their job of serving every customer. Moreover, managers must properly train each service crew to provide a better quality service to every customer and help them with some differences that they experience.